1989
DOI: 10.1038/bjc.1989.395
|View full text |Cite|
|
Sign up to set email alerts
|

A specialist leukaemia/lymphoma registry in the UK. Part 1: incidence and geographical distribution of Hodgkin's disease

Abstract: Summary This paper describes the epidemiology of Hodgkin's disease occurring in parts of the United Kingdom between 1984 and 1986. The cases were carefully diagnosed and the data rigorously cross-checked as part of the larger Leukaemia Research Fund Data Collection Survey of all lymphoid and haematogenous malignancies. The age-specific rates show the lack of an older adult second peak. Spatial variation is examined in some detail. At county and district levels there is little heterogeneity in the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…7,11 Overall, HD is more common in males but within the young adult age group the incidence in females equals or exceeds that of males. 6,12,13 Over time there appears to have been an increase in young adult HD, and in HDNS, but changes in the opposite direction have been observed for HD in older persons and for HDMC. 14 Spatial clustering of HD appears to be specific to young adults and absent in older people.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,11 Overall, HD is more common in males but within the young adult age group the incidence in females equals or exceeds that of males. 6,12,13 Over time there appears to have been an increase in young adult HD, and in HDNS, but changes in the opposite direction have been observed for HD in older persons and for HDMC. 14 Spatial clustering of HD appears to be specific to young adults and absent in older people.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 The distribution of the histological subtypes of HD also varies with age; nodular sclerosis HD (HDNS) largely accounts for the young adult age incidence peak whereas the incidence of mixed cellularity HD (HDMC) increases with age and eventually exceeds that of HDNS. 6,7 In comparison to young adult HD, HDMC is relatively more common than HDNS in childhood. 2,6 Lymphocyte-depleted (HDLD) and lymphocyte predominance HD (HDLP) account for only a small proportion of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for a viral aetiology comes from anecdotal reports of micro-clusters and of case linkage (Vianna et al, 1971;Grufferman et al, 1977), from school cohort studies (Vianna & Polan, 1973), formal analyses of space-time interaction (Kryscio et al, 1973;Greenberg et al, 1983), case-control studies of social linkage (Zack et al, 1977;Scherr et al, 1984), and follow-up of cases of infectious mononucleosis (Rosendahl, 1974; Muellar, 1987). Although the evidence is inconclusive and somewhat conflicting there is a consensus that an infectious aetiology is more likely for younger cases.The Leukaemia Research Fund data collection survey has been described (McKinney et al, 1989) and the basic descriptive epidemiology of Hodgkin's disease reported. This showed some evidence of localised aggregations of cases, or 'clustering', for the younger age group.…”
mentioning
confidence: 99%
“…The Leukaemia Research Fund data collection survey has been described (McKinney et al, 1989) and the basic descriptive epidemiology of Hodgkin's disease reported. This showed some evidence of localised aggregations of cases, or 'clustering', for the younger age group.…”
mentioning
confidence: 99%